2022
DOI: 10.3390/ijms23126770
|View full text |Cite
|
Sign up to set email alerts
|

Bioconjugated Thymol-Zinc Oxide Nanocomposite as a Selective and Biocompatible Antibacterial Agent against Staphylococcus Species

Abstract: Owing to the rapid spread of antibiotic resistance among Staphylococcus species, effective and low-risk alternatives to antibiotics are being actively searched. Thymol (THO), the most abundant component of the oil extracted from thyme, can be considered as a natural antibacterial alternative. However, the low antibacterial activity and non-selectivity of THO limit its usage as a universal anti-Staphylococcus agent. Herein, we report the bioconjugation of THO with ZnO nanoparticle (ZO), which resulted in the TZ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…We have previously reported strong antimicrobial activity of chitosan or alginate-based films with ZnO and citronella essential oil [13,67]. The literature also reported some antibacterial nanocomposites with thyme essential oil used in specific applications [81,82]. In addition, some packaging films containing ZnO and cinnamon essential oils have been reported lately [83,84].…”
Section: Antibacterial Activity Assaymentioning
confidence: 99%
“…We have previously reported strong antimicrobial activity of chitosan or alginate-based films with ZnO and citronella essential oil [13,67]. The literature also reported some antibacterial nanocomposites with thyme essential oil used in specific applications [81,82]. In addition, some packaging films containing ZnO and cinnamon essential oils have been reported lately [83,84].…”
Section: Antibacterial Activity Assaymentioning
confidence: 99%
“…[19][20][21][22][23] Inorganic materials such as ZnO and TiO 2 also have limitations such as low selectivity and cytotoxicity, requiring the strategies to enhance their cell selectivity to broaden their application range. 24,25 Antimicrobial peptides (AMPs) are promising antibiotic alternative candidate with excellent selectivity. They possess a positive surface charge, typically ranging from +2 mv to +11 mv.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that coating or conjugating ZnO-NPs could improve/enhance their biological functions, biocompatibility, and feasibility for the formulation for in vivo use. ZnO-NPs were coated with curcumin, cinnamaldehyde, thymol, tannic acid, salicylic acid, and others [ [13] , [14] , [15] , [16] ] . The use of ZnO@Eug nanocomposites as dental sealants has been demonstrated in several studies.…”
Section: Introductionmentioning
confidence: 99%